Amorphous precursor powder, molded product obtained by molding amorphous precursor powder, method for producing amorphous precursor powder, method for producing sintered molded product, and method for producing powder
By adjusting the molar ratio of lithium, aluminum, and phosphorus in the amorphous precursor powder for all-solid-state batteries, the porosity of the sintered bodies is reduced, addressing the short-circuiting issue and enhancing battery capacity through improved ionic conductivity.
Patent Information
- Application Number
- JP2023101003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-08
AI Technical Summary
Existing methods for producing a solid electrolyte layer in all-solid-state batteries using amorphous LAGP powder result in high porosity sintered bodies, which can lead to short-circuiting when the layer is made thin to enhance battery capacity.
Adjusting the molar ratio of lithium, aluminum, and phosphorus in the amorphous precursor powder to exceed stoichiometric composition, specifically using the formula Li:Al:Ge:P=(1+x+z):x:(2-x):(3+y) with 0.0
The adjusted composition significantly reduces porosity in the sintered molded body, enhancing ionic conductivity and ensuring a solid electrolyte layer with low porosity, thus preventing short-circuiting and improving battery capacity.
Smart Images

Figure 2025001418000001_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an amorphous precursor powder, a molded body obtained by molding the amorphous precursor powder, a method for producing the amorphous precursor powder, a method for producing a sintered molded body, and a method for producing a powder.
Background Art
[0002] As a material for a solid electrolyte of an all-solid-state battery, a solid electrolyte powder having a NASICON-type crystal structure with high ionic conductivity is used. And, as one of the oxide-based lithium ion conductors which are solid electrolytes having a NASICON-type crystal structure, LAGP (=Li 1+x Al x Ge 2-x (PO4)3, where 0 < x ≤ 1.0) is known. On the other hand, amorphous LAGP has been proposed for the purpose of effectively forming a coating of a solid electrolyte on the surface of particles of a powdery electrode active material.
[0003] For example, Patent Document 1 proposes a method for obtaining an amorphous LAGP powder, which is a precursor capable of obtaining a lithium ion conductive oxide powder having a NASICON-type crystal structure that exhibits high ionic conductivity by crystallization. [[ID=2,6]]
[0004] On the other hand, Patent Document 2 describes an all-solid-state battery in which a plurality of laminated units each including a first current collector layer, a solid electrolyte layer made of a solid electrolyte having a NASICON-type crystal structure with high conductivity and being stable in the atmosphere, and a second current collector layer are laminated. From the viewpoint of ensuring the battery capacity of the all-solid-state battery, it is described that the thinner the solid electrolyte layer, the more preferable.
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
Patent Document 2
[0006] In order to increase the ionic conductivity and secure the battery capacity in an all-solid-state battery, it has been considered to adopt a solid electrolyte having a NASICON-type crystal structure that exhibits high ionic conductivity by calcining and crystallizing the amorphous LAGP powder described in Patent Document 1 into the solid electrolyte layer of the all-solid-state battery having the laminated structure described in Patent Document 2.
[0007] The present inventors prepared a powder compact using amorphous LAGP powder as described in Patent Document 1, and then fired it to prepare a sintered compact (sometimes referred to as a "sintered compact" in the present invention). However, it was found that the prepared sintered compact had a high porosity. Here, as described in Patent Document 2, if the solid electrolyte layer composed of a sintered compact with a high porosity is thinned in an all-solid-state battery, the battery may short-circuit.
[0008] The present invention has been made under the above-mentioned circumstances, and the problem to be solved by the present invention is to provide an amorphous precursor powder (sometimes referred to as "amorphous precursor powder" in the present invention) that can be calcined to crystallize to obtain a powder having a NASICON-type crystal structure as a main phase, which exhibits high ionic conductivity, and that can be molded into a molded body and then sintered to obtain a sintered molded body with low porosity. The present invention also provides an amorphous precursor powder, a method for manufacturing the same, the molded body, a method for manufacturing the sintered molded body, and a method for manufacturing the powder having a NASICON-type crystal structure as a main phase. [Means for solving the problem]
[0009] To solve the above problems, as a result of research by the present inventors, in an amorphous precursor powder containing lithium, aluminum, germanium, and phosphorus, the composition ratio is such that, in the general formula Li of LAGP having a NASICON-type crystal structure 1+x Al x Ge 2-x P3O 12 which is expressed as and is a proportional formula of the molar ratios of the respective atoms of lithium, aluminum, germanium, and phosphorus with a stoichiometric composition of 0 < x ≦ 1.0, the composition contains an excess of lithium atoms and phosphorus atoms as compared to Li:Al:Ge:P = (1 + x):x:(2 - x):3, and when the amorphous precursor is molded and fired to obtain a sintered molded body serving as a solid electrolyte layer, it was found that the porosity of the sintered molded body can be reduced (density improved).
[0010] Based on this finding, in the amorphous precursor powder according to the present invention, the molar ratio of lithium atoms and the molar ratio of phosphorus atoms are made excessive within a predetermined range as compared to the molar ratio of the above-described stoichiometric composition, and it was conceived to make the molar ratio (P / Li) of lithium atoms and phosphorus atoms made excessive from the stoichiometric composition within a predetermined range.
[0011] That is, a first invention for solving the above problems is an amorphous precursor powder containing lithium, aluminum, germanium, and phosphorus, where the molar ratios of the respective atoms of lithium, aluminum, germanium, and phosphorus are expressed by the proportional formula Li:Al:Ge:P = (1 + x + z):x:(2 - x):(3 + y), and the x, y, and z in the proportional formula are such that 0.0 < x ≦ 1.0, 0.1 ≦ y ≦ 0.8, and 0.2 ≦ y / z ≦ 0.8. A second invention is the amorphous precursor powder according to the first invention, where the value of y is 0.1 ≦ y ≦ 0.5. A third invention is When the XRD measurement is performed on the powder obtained by heat-treating 10 g of the amorphous precursor powder at 600° C. for 120 minutes in an air atmosphere, it is confirmed that the amorphous precursor powder according to the first or second invention has a NASICON-type crystal structure as a main phase. The fourth invention is the amorphous precursor powder according to the first or second invention, wherein the value of z satisfies 0.125 ≦ z ≦ 2.0. The fifth invention is a molded body obtained by molding the amorphous precursor powder according to the first or second invention. The sixth invention is a method for producing an amorphous precursor powder which becomes a powder having a NASICON-type crystal structure as a main phase by heat-treating at 600° C. for 120 minutes in an air atmosphere, the method comprising: a step of obtaining a slurry containing lithium, aluminum, germanium, and phosphorus; a firing step of firing the slurry at 300° C. or higher and 500° C. or lower to obtain an amorphous precursor powder, in the slurry, the molar ratio of each atom of lithium, aluminum, germanium, and phosphorus is represented by a proportional formula Li:Al:Ge:P = (1 + x + z):x:(2 - x):(3 + y), wherein the slurry is prepared such that x, y, and z in the proportional formula satisfy 0.0 < x ≦ 1.0, 0.1 ≦ y ≦ 0.8, and 0.2 ≦ y / z ≦ 0.8. The seventh invention is the method for producing an amorphous precursor powder according to the sixth invention, wherein the step of obtaining the slurry includes a step of mixing an aqueous solution containing germanium and an aqueous solution containing lithium, aluminum, and phosphorus. The eighth invention is the method for producing an amorphous precursor powder according to the seventh invention, wherein the pH value of the aqueous solution containing lithium, aluminum, and phosphorus is pH 1 or higher and pH 5.5 or lower. The ninth invention is the method for producing an amorphous precursor powder according to the sixth or seventh invention, wherein the pH value of the slurry is pH 1 or higher and pH 6.5 or lower. The tenth invention is This is a method for producing a sintered molded body, in which a powder produced by the method for producing an amorphous precursor powder described in the sixth or seventh invention is compression-molded and then sintered to produce a sintered molded body having a NASICON-type crystal structure as a main phase. The eleventh invention is This is a method for producing a powder, which comprises calcining a powder produced by the method for producing an amorphous precursor powder according to the sixth or seventh invention, to produce a powder having a NASICON-type crystal structure as a main phase. [Effects of the Invention]
[0012] By calcining and crystallizing the amorphous precursor powder according to the present invention, which contains excess lithium and phosphorus atoms relative to the stoichiometric composition, a powder having a NASICON-type crystal structure as the main phase, which exhibits high ionic conductivity, can be obtained. It has also been found that the porosity of a sintered body obtained by molding the amorphous precursor powder according to the present invention and firing it at 800°C is significantly lower than the porosity of a sintered body obtained by molding the amorphous precursor powder having a stoichiometric composition and firing it at 800°C. [Brief explanation of the drawings]
[0013] [Figure 1] FIG. 1 is a flow chart showing the production process of an amorphous precursor powder and a sintered compact according to the present invention. [Figure 2] 1 is an XRD spectrum of the amorphous precursor powder according to Example 1. [Figure 3] (Top) XRD spectrum of powder having a NASICON-type crystal structure as a main phase according to Example 1, (bottom) XRD spectrum of powder having a NASICON-type crystal structure as a main phase according to Comparative Example 1. [Figure 4] 1 shows (top) an XRD spectrum of the white precursor powder after the drying process according to Example 1, and (bottom) an XRD spectrum of the white precursor powder after the drying process according to Comparative Example 1. DETAILED DESCRIPTION OF THE INVENTION
[0014] The embodiments for carrying out the present invention will be described in the following order: 1. the amorphous precursor powder according to the present invention; 2. the amorphous precursor powder according to the present invention and a method for producing a sintered molded body using the amorphous precursor powder; and 3. evaluation of the amorphous precursor powder and sintered molded body according to the present invention.
[0015] 1. Amorphous precursor powder according to the present invention The amorphous precursor powder containing lithium, aluminum, germanium, and phosphorus according to the present invention is a precursor of a powder and a sintered compact having a NASICON-type crystal structure, which can be obtained by firing and crystallizing the powder and the sintered compact having a NASICON-type crystal structure as the main phase, exhibiting high ionic conductivity.
[0016] When the amorphous precursor powder according to the present invention containing lithium, aluminum, germanium, and phosphorus is subjected to powder X-ray diffraction (also referred to as XRD in the present invention), a halo is observed in the XRD spectrum in the 2θ:10° to 60° region. The "halo" does not exhibit a clear peak, but is a gradual fluctuation in X-ray intensity, which is observed as a broad rise in the X-ray chart. The half-width of the halo is 2θ:2° or more.
[0017] For example, when the amorphous precursor powder of the present invention is subjected to "2. Method for producing amorphous precursor powder of the present invention, (5) (precursor powder) calcination step, (II) crystallization of amorphous precursor powder" in "Example 1" described below, the resulting powder has a NASICON-type crystal structure as the main phase. The powder having the NASICON-type crystal structure as the main phase has, in the XRD spectrum obtained by XRD measurement, an X-ray diffraction peak of an oxide having the NASICON-type crystal structure as the main phase. Here, the "main phase" refers to the crystalline phase to which the most intense diffraction peak belongs in the XRD spectrum obtained by XRD measurement.
[0018] Whether the diffraction peak can be attributed or not can be determined by comparing the XRD spectrum of the powder having the NASICON-type crystal structure as the main phase with the diffraction peaks of the oxides having the NASICON-type crystal structure registered in the database. For example, for the oxide LiGe2P3O having the NASICON-type crystal structure 12 The diffraction peaks can be determined by comparing with PDF (Powder Diffraction File) No. 01-080-1922 of ICDD (International Centre for Diffraction Data).
[0019] More specifically, when the XRD spectrum of the powder having the NASICON-type crystal structure as the main phase is compared with the ICDD's PDF No. 01-080-1922 of the oxide having the NASICON-type crystal structure, if the peaks detected by the peak search method are in the range of 21.4±0.5, 25.1±0.5°, 30.4±0.5°, 33.3±0.5°, 34.0°±0.5°, it can be determined that it is the crystal phase attributed to PDF No. 01-080-1922.
[0020] The amorphous precursor powder containing lithium, aluminum, germanium, and phosphorus according to the present invention has a composition ratio that, compared with the proportional formula of the molar ratios of the respective atoms of lithium, aluminum, germanium, and phosphorus in the stoichiometric composition of LAGP having the NASICON-type crystal structure, Li 1+x Al x Ge 2-x P3O 12 represented as and 0 < x ≤ 1.0, contains an excess of lithium atoms and phosphorus atoms, and thus has a composition ratio deviated from the stoichiometric composition (so-called LAGP).
[0021] The amorphous precursor powder containing lithium, aluminum, germanium, and phosphorus according to the present invention has a molar ratio of germanium to aluminum in the amorphous precursor powder fixed at 2, and the molar ratios of the atoms of lithium, aluminum, germanium, and phosphorus are represented by the proportional formula Li:Al:Ge:P = (1 + x + z):x:(2 - x):(3 + y) (where x, y, and z in the proportional formula satisfy 0.0 < x ≤ 1.0, 0.1 ≤ y ≤ 0.8, and 0.2 ≤ y / z ≤ 0.8).
[0022] When the amorphous precursor powder containing lithium, aluminum, germanium, and phosphorus is formed and fired to obtain a molded body serving as a solid electrolyte layer, the density of the molded body can be improved (the porosity can be reduced).
[0023] In the proportional formula of the amorphous precursor powder of the present invention, x serves as an index of the aluminum content in the amorphous precursor powder. It is preferably 0.0 < x ≤ 1.0, more preferably 0.1 ≤ x ≤ 0.9, and most preferably 0.2 ≤ x ≤ 0.7. The Ge 4+ ionic radius and the Al 3+ ionic radius are both the same at 0.39 Å, and in the range of 0 < x ≤ 1.0, Ge sites can arbitrarily dissolve Al. The purpose of dissolving Al is charge compensation, and it is generally used in the range of 0.2 ≤ x ≤ 0.7 for the purpose of increasing the carrier density of Li. y serves as an index of the excess amount of phosphorus atoms with respect to the molar ratios of the atoms of lithium, aluminum, germanium, and phosphorus in the stoichiometric composition of LAGP having a NASICON-type crystal structure. It is preferably 0.1 ≤ y ≤ 0.8, and more preferably 0.1 ≤ y ≤ 0.5. z serves as an index of the excess amount of lithium atoms with respect to the molar ratios of the atoms of lithium, aluminum, germanium, and phosphorus in the stoichiometric composition of LAGP having a NASICON-type crystal structure. It is preferably 0.125 ≤ z ≤ 2.0, more preferably 0.15 ≤ z ≤ 1.5, and even more preferably 0.2 ≤ z ≤ 1.3. Furthermore, y / z is the ratio of the excess amount of lithium to the excess amount of phosphorus (P / Li), and y / z is preferably 0.2≦y / z≦0.8, and more preferably 0.2≦y / z≦0.5.
[0024] The amorphous precursor powder contains lithium, aluminum, germanium, phosphorus, oxygen, and, if necessary, other elements. The contents of these elements are not particularly limited as long as the amorphous precursor powder can be sintered and crystallized to obtain a powder and a sintered compact having a NASICON-type crystal structure as the main phase, which exhibits high ionic conductivity. However, from the viewpoint of obtaining a powder and a sintered compact having a NASICON-type crystal structure as the main phase, which exhibits higher ionic conductivity, the contents of each element in the amorphous precursor powder are preferably within the following ranges.
[0025] Lithium is an element that contributes to the formation of a NASICON-type crystal structure when the amorphous precursor powder is crystallized. The lower limit of the lithium content is preferably 1.0 mass% or more, more preferably 1.5 mass% or more, and even more preferably 1.8 mass% or more. The upper limit is preferably 10.0 mass% or less, more preferably 8.0 mass% or less, even more preferably 5.0 mass% or less, and most preferably 4.0 mass% or less.
[0026] Aluminum is an element that contributes to the formation of a NASICON-type crystal structure when the amorphous precursor powder is crystallized. The lower limit of the aluminum content is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and even more preferably 2.0% by mass or more. The upper limit is preferably 6.0% by mass or less, more preferably 5.0% by mass or less, and even more preferably 4.0% by mass or less.
[0027] Germanium is an element that contributes to the formation of amorphous in the amorphous precursor powder and also contributes to the formation of a NASICON-type crystal structure when the amorphous precursor powder is crystallized. The lower limit of the germanium content is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 21% by mass or more. The upper limit is preferably 35% by mass or less, more preferably 30% by mass or less, and even more preferably 28% by mass or less.
[0028] Phosphorus is an element that contributes to the formation of amorphous in the amorphous precursor powder and also contributes to the formation of a NASICON-type crystal structure when the amorphous precursor powder is crystallized. The lower limit of the phosphorus content is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more. The upper limit is preferably 30% by mass or less, more preferably 28% by mass or less, and even more preferably 25% by mass or less.
[0029] The amorphous precursor powder may contain elements other than the above-mentioned lithium, aluminum, germanium, phosphorus, and oxygen, as long as the effects of the present invention are not impaired. The total content of elements other than lithium, aluminum, germanium, phosphorus, and oxygen in the amorphous precursor powder is preferably 5% by mass or less, and more preferably 3% by mass or less.
[0030] Oxygen becomes the balance of lithium, aluminum, germanium, phosphorus, and other elements. That is, the oxygen content is the amorphous precursor powder minus the total content of each of the above-mentioned constituent elements (100 mass% - total mass% of each constituent element), and is preferably 40 mass% or more and 55 mass% or less.
[0031] As will be described later in the "Examples" section, a sintered body obtained by molding an amorphous precursor powder having a stoichiometric composition and firing it at 800°C had a porosity of 33%, whereas a sintered body obtained by molding an amorphous precursor powder according to the present invention containing lithium atoms and phosphorus atoms in excess of the stoichiometric composition and firing it at 800°C had a porosity of 21 to 24%, a significant decrease in porosity. In other words, the amorphous precursor powder according to the present invention containing lithium atoms and phosphorus atoms in excess of the stoichiometric composition is an amorphous precursor powder that can yield a sintered body having a porosity of 30% or less, which is required as a solid electrolyte layer in an all-solid-state battery.
[0032] The reason for the reduced porosity of this sintered molded body is presumably that the amorphous precursor powder according to the present invention contains an excess of lithium and phosphorus, and during sintering, the excess lithium and phosphorus act as sintering aids, melting and sintering the lithium and phosphorus and filling the voids in the sintered molded body, thereby significantly reducing the porosity of the sintered molded body after sintering at 800°C.
[0033] Generally, when a sintering aid is used, the material to be sintered and the sintering aid are mixed uniformly before sintering. However, in the present invention, by using an amorphous precursor powder containing lithium atoms and phosphorus atoms in excess of the stoichiometric composition, it is possible to omit the step of adding and uniformly mixing the sintering aid before sintering.
[0034] In the present invention, the reason for firing at 800°C to obtain a sintered compact is that a firing temperature of 900°C or less is preferred when fabricating a laminated battery using a green sheet made using a solid electrolyte (see, for example, Patent Document 2).
[0035] 2. Amorphous precursor powder according to the present invention and method for producing a sintered compact using the amorphous precursor powder The amorphous precursor powder according to the present invention can be obtained by mixing aqueous solutions of raw materials containing the respective constituent elements to obtain a slurry, and then firing the slurry at a predetermined temperature.
[0036] The following describes the manufacturing method of the amorphous precursor powder and sintered compact according to the present invention, in the order of (1) preparing a germanium aqueous solution, (2) preparing a lithium, aluminum, and phosphorus aqueous solution, (3) mixing (preparing a raw material slurry), (4) drying, and (5) firing (precursor powder) with reference to the manufacturing flow diagram of Figure 1. Next, an example of the manufacturing method of the sintered compact according to the present invention will be described in the order of (6) particle size adjustment, (7) molding (manufacturing a compact), and (8) firing (a compact).
[0037] (1) Preparation of germanium aqueous solution This is a step of mixing a germanium compound powder into pure water to prepare an aqueous solution containing germanium. In this case, it is preferable to use GeO2 as the germanium compound and further add ammonia water to prepare an aqueous solution containing germanium. By dissolving GeO2 in ammonia water, germanium is converted into (NH4)3HGe7O after the drying process described later. 16 It is believed that the germanium remains in a complex state in the dry powder, which is the powder before calcination of the amorphous precursor powder described below, and this is thought to inhibit the generation of GeO2 during calcination of the powder before calcination.
[0038] (2) Preparation of lithium, aluminum, and phosphorus aqueous solutions This is a process in which a lithium compound powder, an aluminum compound powder, and a phosphorus compound solution are mixed with pure water to prepare an aqueous solution containing lithium, aluminum, and phosphorus. In this case, examples of lithium compound powders include LiNO3, Li2SO4, Li2CO3, and LiCl. Examples of aluminum compound powders include Al(NO3)3, Al2(SO4)3, Al2(CO3)3, and AlCl3. Examples of phosphorus compound aqueous solutions include (NH4)H2PO4 aqueous solution, (NH4)2HPO4 aqueous solution, H3PO4 aqueous solution, and (NH4)3PO4 aqueous solution.
[0039] When preparing an aqueous solution containing lithium, aluminum, and phosphorus, the molar ratios of the atoms of lithium, aluminum, and phosphorus contained in the slurry containing lithium, aluminum, germanium, and phosphorus, which will be described later, are such that in the proportional formula Li:Al:P = (1 + x + z):x:(3 + y), x, y, and z in the proportional formula are adjusted so that 0.0 < x ≤ 1.0, 0.1 ≤ y ≤ 0.8, and 0.2 ≤ y / z ≤ 0.8. Incidentally, at this time, it is preferable that 0.1 ≤ x ≤ 0.9, more preferably 0.2 ≤ x ≤ 0.7. It is preferable that 0.1 ≤ y ≤ 0.5. It is preferable that 0.125 ≤ z ≤ 2.0, more preferably 0.15 ≤ z ≤ 1.5, and even more preferably 0.2 ≤ z ≤ 1.3. It is preferable that 0.2 ≤ y / z ≤ 0.5.
[0040] Since the compounds of lithium, aluminum, and phosphorus are acidic, it is preferable that the aqueous solution containing lithium, aluminum, and phosphorus also has an acidic property. This is because when the aqueous solution is on the alkaline side, it is considered that crystalline Li3PO4 may be formed. In order to prevent the added lithium and phosphorus from becoming crystalline Li3PO4 and containing a secondary phase different from the amorphous precursor powder according to the present invention, the preferable range of the pH value of the aqueous solution containing lithium, aluminum, and phosphorus is pH 1 to 5.5.
[0041] (3) Mixing (Preparation of Raw Material Slurry) Step This is a step of mixing the two types of aqueous solutions prepared in the above “(1) Preparation Step of Aqueous Germanium Solution, (2) Preparation Step of Aqueous Lithium, Aluminum, and Phosphorus Solution” to obtain a slurry containing the constituent elements of the amorphous precursor powder. For example, when an aqueous solution containing acidic lithium, aluminum, and phosphorus is added to an aqueous solution containing alkaline germanium dissolved in ammonia, it immediately becomes turbid, and a slurry containing lithium, aluminum, germanium, and phosphorus can be obtained by coprecipitation. In this mixing step, there is no particular need to consider the liquid temperature, and it may or may not be heated. It is considered that in the slurry, there are constituent elements precipitated as hydroxides and constituent elements present as ions.
[0042] Realizing a supersaturated state where the ion concentration product of the constituent elements is higher than the solubility product and generating a slurry using the coprecipitation method is essential for obtaining an amorphous precursor powder to improve the uniformity of the constituent elements. During mixing, the molar ratios of the atoms of lithium, aluminum, germanium, and phosphorus are adjusted so that the proportional formula Li:Al:Ge:P = (1 + x + z):x:(2 - x):(3 + y) holds. At this time, x is adjusted to be 0.0 < x ≤ 1.0, and y and z are adjusted to be 0.1 ≤ y ≤ 0.8 and 0.2 ≤ y / z ≤ 0.8. Furthermore, at this time, x is preferably 0.1 ≤ x ≤ 0.9, and most preferably 0.2 ≤ x ≤ 0.7. y is preferably 0.1 ≤ y ≤ 0.8, and more preferably 0.1 ≤ y ≤ 0.5. z is preferably 0.125 ≤ z ≤ 2.0, more preferably 0.15 ≤ z ≤ 1.5, and still more preferably 0.2 ≤ z ≤ 1.3. y / z is preferably 0.2 ≤ y / z ≤ 0.5.
[0043] Note that from the perspective of avoiding the formation of the above-described crystalline Li3PO4, it is preferable to maintain acidity in the slurry as well. For example, the preferable range of the pH value of the slurry is pH 1 to 6.5. More preferably, it is pH 2 to 5.
[0044] (4) Drying step This is a step of drying the moisture of the slurry obtained in the above-mentioned “(3) Mixing (Preparation of raw material slurry) step” to obtain a dried powder which is a powder before firing of the amorphous precursor powder. The drying step is not an essential operation, but the quality is more stable than directly firing the slurry. The drying method is not particularly limited, but spray drying using a spray dryer or the like is preferred. Spray drying rapidly precipitates the constituent elements present as ions in the slurry in a short period of time, thereby reducing the non-uniformity of precipitation resulting from differences in the solubility of the constituent elements. This allows for the production of a dry powder with a uniform composition, which is a pre-calcination powder of the amorphous precursor powder in which GeO2 generation is suppressed, more reliably. The drying temperature may be appropriately set so that no moisture remains in the resulting pre-calcination powder of the amorphous precursor powder.
[0045] When the obtained dry powder is subjected to XRD measurement, it is preferable that the XRD spectrum does not show peaks of lithium compounds, aluminum compounds, germanium compounds, or phosphorus compounds in the 2θ: 10° to 60° region.
[0046] (5) (Precursor powder) firing process This is a step of calcining the pre-calcined amorphous precursor powder obtained in the "(4) drying step" to obtain an amorphous precursor powder. Specifically, the temperature is increased from room temperature to 300°C or higher and 500°C or lower, preferably 400°C, at a rate of 0.1°C / min or higher and 20°C / min or lower in an air atmosphere, and then the material is calcined by holding the material at that temperature for 120 minutes in an air atmosphere, thereby obtaining the amorphous precursor powder according to the present invention.
[0047] (6) Particle size adjustment process In the production of the sintered compact of the present invention, the amorphous precursor powder of the present invention may be used as is, or the particle size and specific surface area may be appropriately adjusted as desired. Although known methods can be used to adjust the particle size and specific surface area, wet pulverization using a bead mill or the like is preferred.
[0048] The particle size and specific surface area in wet grinding using a bead mill can be adjusted appropriately by known methods, such as by adjusting the material of the media (beads), the diameter of the media (beads), the ratio of media (beads) to slurry, the slurry concentration, the grinding time, and the rotation speed. When wet pulverization is carried out, solid-liquid separation is carried out after the wet pulverization treatment, and the recovered amorphous precursor powder after wet pulverization is dried. The particle size of the amorphous precursor powder according to the present invention is preferably such that the volume-based cumulative 50% particle size (D50) is 0.1 μm or more and 10 μm or less.
[0049] As a solvent for wet milling, an organic solvent is preferred to prevent ion exchange of lithium in the amorphous precursor powder with protons, which would reduce the ionic conductivity of the molded solid electrolyte body. Specifically, IPA (isopropyl alcohol) is preferred. This is because IPA volatilizes during drying after milling and does not remain in the amorphous precursor powder. When a bead mill is used for milling, alumina or zirconia is preferred as the bead material to prevent impurities from being mixed in. The amorphous precursor powder after wet milling is preferably dried at a temperature above the boiling point of the solvent used and below the firing temperature in the "(8) (Molded Body) Calcination Step" described below to remove the solvent used. Furthermore, if the moisture content of the obtained amorphous precursor powder is excessively low, a step of adjusting the moisture content of the powder by exposing it to a moisture-containing atmosphere for a predetermined time may be included.
[0050] (7) Molding (manufacturing of molded bodies) process The produced amorphous precursor powder according to the present invention is filled into a molding die, and then compressed and molded under pressure to produce a molded body. The pressure during compression molding is preferably 1 MPa to 300 MPa, and compression molding is preferably carried out for 1 second to 10 hours. Conventional molding dies and presses can be used.
[0051] (8) (Molded body) firing process Specifically, the molded body is heated from room temperature to 600°C or higher and 900°C or lower at a heating rate of 0.1°C / min or higher and 20°C / min or lower in an air atmosphere, and then maintained at that temperature for 120 minutes in an air atmosphere for firing, thereby obtaining a sintered molded body according to the present invention.
[0052] 3. Evaluation of the amorphous precursor powder and sintered compact according to the present invention The amorphous precursor powder according to the present invention obtained in the above "2. Manufacturing method of amorphous precursor powder according to the present invention, (5) (precursor powder) firing step" was subjected to composition analysis and XRD measurement. Next, the sintered molded body according to the present invention obtained in the "(8) (molded body) firing step" was subjected to porosity measurement. Specific details regarding the composition analysis of the amorphous precursor powder, the XRD measurement, and the porosity measurement of the sintered compact will be described later in the Examples. [Example]
[0053] Example 1 The amorphous precursor powder of Example 1 was produced according to the flow chart showing the manufacturing process of the amorphous precursor powder. The manufactured amorphous precursor powder of Example 1 was then analyzed and characterized. The process will be explained in the following order: (1) preparation process of a germanium aqueous solution, (2) preparation process of a lithium, aluminum, and phosphorus aqueous solution, (3) mixing (preparation of raw material slurry), (4) drying process, (5) (precursor powder) calcination process, and [analysis and characteristic evaluation of the amorphous precursor powder]. Next, the amorphous precursor powder according to Example 1 thus produced was used to produce a sintered molded body according to Example 1, and its properties were evaluated. (7) The molding (production of molded body) step, (8) (molded body) firing step, and [Property evaluation of sintered molded body] will be described in this order.
[0054] (1) Preparation of germanium aqueous solution 30.7 g of germanium dioxide (99.999% manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 614 g of pure water and heated to 40°C with stirring. To the heated liquid, 15.0 g of 28% by mass aqueous ammonia (28% by weight, manufactured by Nacalai Tesque) was added as an alkali. After the addition of aqueous ammonia, the mixture was stirred while being heated to 40°C and aged for 10 minutes. A 659.7 g transparent aqueous solution containing germanium was prepared, the formulation of which is shown in Table 1.
[0055] (2) Preparation of lithium, aluminum, and phosphorus aqueous solutions To 150 g of pure water, 24.7 g of lithium nitrate (99.9% by Fujifilm Wako Pure Chemical Industries, Ltd.), 36.7 g of aluminum nitrate nonahydrate (99.9% by Fujifilm Wako Pure Chemical Industries, Ltd.), and 70.1 g of ammonium dihydrogen phosphate (99+% by Fujifilm Wako Pure Chemical Industries, Ltd.) were added to prepare an aqueous solution containing lithium, aluminum, and phosphorus. The pH value of the prepared lithium, aluminum, and phosphorus-containing aqueous solution was 1.4, making it acidic. The composition and pH value are shown in Table 1.
[0056] (3) Mixing (preparation of raw material slurry) process The germanium-containing aqueous solution was heated to 40°C while stirring, and the entire amount (281.5 g) of the acidic lithium-, aluminum-, and phosphorus-containing aqueous solution was added thereto and mixed. The aqueous solution became cloudy immediately after the addition, and a white raw material slurry was obtained. The obtained white raw material slurry was stirred and aged for 10 minutes while heated to 40°C. The pH value of the obtained raw material slurry was 4.3. The pH value is shown in Table 1.
[0057] The molar amount of each element in the raw material slurry was calculated from the charged composition. These values are shown in Table 2. Next, the total value of the aluminum molar ratio and the germanium molar ratio was fixed at 2, and the converted molar ratio values of each element were substituted into the proportional equation Li:Al:Ge:P=(1+x+z):x:(2-x):(3+y) to derive the values of x, y, z, and y / z. These values are listed in Table 2.
[0058] (4) Drying process The raw material slurry was spray-dried using a spray dryer (SD-1000 manufactured by Tokyo Rikakikai Co., Ltd.) to evaporate the water in the raw material slurry and precipitate it into a solid phase at once, thereby obtaining a white precursor powder. The spray-drying conditions were an inlet temperature of 180°C, an outlet temperature of 90°C, and a raw material slurry addition rate of 10 g / min.
[0059] (5) (Precursor powder) firing process The white precursor powder according to Example 1 obtained by the spray drying was subjected to "(I) Preparation of amorphous precursor powder" described below, to obtain the amorphous precursor powder according to Example 1. Next, in order to evaluate the characteristics of the amorphous precursor powder of Example 1, the amorphous precursor powder was crystallized by carrying out the "(II) Crystallization of amorphous precursor powder" described below, to obtain a crystallized powder.
[0060] (I) Preparation of amorphous precursor powder 10 g of the precursor powder obtained by the spray drying was placed in an alumina container, and the temperature was increased from room temperature to 400°C at a rate of 5°C / min in an air atmosphere, and the mixture was fired at 400°C for 120 minutes, thereby obtaining an amorphous precursor powder according to Example 1.
[0061] (II) Crystallization of amorphous precursor powder 10 g of the amorphous precursor powder of Example 1 was placed in an alumina container, and the temperature was increased from room temperature to 600°C at a rate of 5°C / min in an air atmosphere, and heat-treated at 600°C for 120 minutes to crystallize the amorphous precursor powder.
[0062] [Analysis and characterization of amorphous precursor powders] The amorphous precursor powder according to Example 1 obtained in the above-mentioned "(5) (Precursor Powder) Calcination Step, (I) Preparation of Amorphous Precursor Powder" was subjected to composition analysis and XRD measurement. Furthermore, "(5) (Precursor Powder) Calcination Step, (II) Crystallization of Amorphous Precursor Powder" was performed to prepare a powder according to Example 1 having a NASICON-type crystal structure as a main phase, and XRD measurement was performed. Each method and result will be explained below.
[0063] (composition analysis) Sodium carbonate was added as a melting agent to the amorphous precursor powder of Example 1 to prepare an alkali molten salt. The alkali molten salt was dissolved in nitric acid, and the resulting solution was subjected to elemental analysis using an ICP-OES device (ICP-720, manufactured by Agilent). The quantitative analysis values (mass%) of the constituent elements of lithium, aluminum, germanium, and phosphorus were 3.0 mass% for lithium, 3.1 mass% for aluminum, 24.2 mass% for germanium, and 22.2 mass% for phosphorus. These values are shown in Table 3.
[0064] Next, the quantitative analysis value (mass%) of each constituent element was divided by the atomic weight of each element, and the values of the quantitative analysis value (mass%) of each constituent element / atomic weight of each constituent element (mass% / atomic weight) were 0.43 mol for lithium, 0.11 mol for aluminum, 0.33 mol for germanium, and 0.72 mol for phosphorus. These values are shown in Table 3.
[0065] From the results of the composition analysis described above, the molar ratios of lithium, aluminum, germanium, and phosphorus atoms in the amorphous precursor powder according to the present invention are shown in Table 3, assuming that the sum of the molar ratios of germanium and aluminum is fixed at 2. Substituting these molar ratios of lithium, aluminum, germanium, and phosphorus atoms into the proportional equation Li:Al:Ge:P=(1+x+z):x:(2-x):(3+y), we derived x=0.5, y=0.2, and z=0.4, resulting in y / z=0.5. These values are shown in Table 4.
[0066] Furthermore, the volume-based cumulative 50% particle size (D50) of the amorphous precursor powder of Example 1 was measured at a dispersion pressure of 5 bar using a laser diffraction / scattering particle size distribution analyzer (SYMPATEC, HELOS & RODOS (airflow dispersion module)) and was found to be 6.0 μm. This value is shown in Table 4.
[0067] (XRD measurement) XRD measurement was carried out under the measurement conditions described below for the amorphous precursor powder of Example 1. The obtained XRD spectrum is shown in FIG. 2, it was confirmed that the amorphous precursor powder (lithium ion conductor) according to Example 1 has an amorphous structure, as a halo was observed in the 2θ:10° to 60° region by XRD measurement.
[0068] In addition, in the XRD spectrum shown in Figure 2, no peaks of the raw material compounds used in preparing the amorphous precursor powder of Example 1 were observed, and no peaks indicating a NASICON-type or other crystal structure were observed.
[0069] The amorphous precursor powder of Example 1, obtained in the above-mentioned "(5) (Precursor Powder) Calcination Step, (II) Crystallization of Amorphous Precursor Powder," was subjected to XRD measurement under the measurement conditions described below. The obtained XRD spectrum is shown in the upper part of Figure 3. The circles (■) shown in the figure indicate diffraction peaks attributable to the NASICON-type crystal structure, and the arrows (▲) shown in the figure indicate diffraction peaks associated with the subphases described below.
[0070] The XRD spectrum of the powder obtained by crystallizing the amorphous precursor powder of Example 1 shown in the upper part of FIG. 3 is obtained by comparing the XRD spectrum of LiGePO, an oxide having a NASICON-type crystal structure, with the XRD spectrum of LiGePO 12 This was compared with ICDD PDF No. 01-080-1922. The diffraction peaks detected by the peak search method were in the ranges of 21.4±0.5°, 25.1±0.5°, 30.4±0.5°, 33.3±0.5°, and 34.0±0.5°, and were determined to belong to PDF No. 01-080-1922. Furthermore, the diffraction peak with the highest intensity in the XRD spectrum was determined to belong to the NASICON-type crystal structure. Therefore, the powder obtained by crystallizing the amorphous precursor powder of Example 1 was found to contain lithium, aluminum, germanium, and phosphorus from the results of the composition analysis described above, and the XRD measurement results indicated that it had a NASICON-type crystal structure as the main phase.
[0071] In addition, as a result of collating the XRD spectra of the powders obtained by crystallizing the amorphous precursor powders according to Examples 2 and 3 and Comparative Examples 1 to 4 described below with PDF No. 01-080-1922 as well, it was found that they belong to No. 01-080-1922. Also, it was found that the diffraction peak with the highest intensity in the XRD spectrum belongs to the NASICON-type crystal structure.
[0072] Next, in the XRD measurement results of the powder obtained by crystallizing the amorphous precursor powder according to Example 1, a diffraction peak of GeO2 was detected near 25.9°, and a secondary phase was confirmed. Therefore, when examining the peak intensity ratio between the strongest peak related to the main phase and the strongest peak related to the secondary phase, the value of the peak intensity ratio of the secondary phase / main phase was 0.2. This result is described in Table 4.
[0073] Also, XRD measurement was carried out under the following measurement conditions for the white precursor powder according to Example 1 obtained in the above-mentioned “(4) Drying step”. The obtained XRD spectrum is shown in the upper part of FIG. 4. In the XRD measurement results, a peak of NH4NO3 was shown, but peaks of lithium compound, aluminum compound, germanium compound, and phosphorus compound were not shown.
[0074] <XRD Measurement Conditions> Measuring device: XRD-6100 (manufactured by Shimadzu Corporation) Tube target: Cu Tube voltage: 40 kv Tube current: 30 mA Divergence slit: 1.0° Scattering slit: 1.0° ; Receiving slit: 0.3 mm Step width: 0.02° / step Measurement time: 0.25 sec Peak search was performed using XRD-�6100 software manufactured by Shimadzu Corporation. The peak search conditions were carried out under the following conditions. Smoothing process: Automatic Background process: Automatic Ka1-a2 ratio: 50 Peak search: Automatic
[0075] (7) Molding (manufacturing of molded bodies) process 0.25 g of the amorphous precursor powder according to Example 1 was weighed out and filled into a mold having a diameter of 11 mm. A load of 105 MPa was applied using a hydraulic press and held for 10 seconds to obtain a compression-molded compact.
[0076] (8) (Molded body) firing process The obtained molded body was placed in a box furnace, heated from room temperature to 800°C at a rate of 5°C / min in an air atmosphere, and fired at 800°C for 2 hours to obtain a sintered molded body according to Example 1.
[0077] [Evaluation of sintered compact properties] The obtained sintered molded body according to Example 1 was dried at 110° C., and the mass of the sintered molded body after drying was measured and designated as the dry mass W1. The obtained sintered molded body was placed at the bottom of a vacuum container, and the vacuum container was evacuated for 15 minutes using a vacuum pump under a gauge pressure of -96 kPa to thoroughly remove air from the pores of the sintered molded body. Next, IPA (isopropyl alcohol) was poured into the vacuum vessel until the sintered compact was completely immersed. Then, the cock attached to the vacuum vessel was gradually opened to restore the gauge pressure inside the vacuum vessel to 0 Pa, and the vessel was left standing for 30 minutes.
[0078] The sintered compact immersed in IPA was suspended by a wire, and the mass of the sintered compact in IPA was measured while suspended. The mass corrected for the amount suspended by the wire was defined as the mass in IPA W2.
[0079] Next, the sintered molded body was taken out of the IPA, and the surface thereof was quickly wiped with gauze moistened with IPA to remove the IPA, and then the mass of the sintered molded body was measured and defined as the saturated mass W3. After the gauze was sufficiently saturated with IPA, it was squeezed to remove only the IPA from the surface of the sintered molded body.
[0080] Using the masses W1 to W3 thus obtained, the porosity Po of the sintered compact according to Example 1 was calculated from (Equation 1) to be 24%. This value is shown in Table 4. Po(%)=(W3-W1) / (W3-W2)×100...(Formula 1) The above-mentioned porosity measurement method was based on JIS R1634.1998 (method of measuring sintered density and open porosity of fine ceramics).
[0081] (Examples 2 and 3) The amorphous precursor powders of Examples 2 and 3 were produced by the same procedure as in Example 1, except that in "(2) Aqueous solution containing lithium, aluminum, and phosphorus" in Example 1, the amount of lithium nitrate (99.9% manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) added and the amount of ammonium dihydrogen phosphate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) added were changed as shown in Table 1. Similarly to Example 1, the amorphous precursor powders of Examples 2 and 3 were analyzed and characterized. Furthermore, the same operations as in Example 1 were carried out to produce sintered molded bodies according to Examples 2 and 3, and the porosity was measured. The pH values of the lithium-, aluminum-, and phosphorus-containing aqueous solutions prepared in Examples 2 and 3, the pH values of the obtained raw material slurries, the compositions in the manufacturing process of the amorphous precursor powders, the analytical results and characteristic evaluation results, and the porosity of the sintered compacts are shown in Tables 1 to 4, similar to Example 1.
[0082] (Comparative Examples 1 to 4) Amorphous precursor powders according to Comparative Examples 1 to 4 were produced by the same procedure as in Example 1, except that in "(2) Aqueous solution containing lithium, aluminum, and phosphorus" in Example 1, the amount of lithium nitrate (99.9% manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) added and the amount of ammonium dihydrogen phosphate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) added were changed as shown in Table 1. Then, similarly to Example 1, the amorphous precursor powders according to Comparative Examples 1 to 4 were analyzed and their properties were evaluated. Furthermore, the same operations as in Example 1 were carried out to produce sintered molded bodies according to Comparative Examples 1 to 4, and the porosity was measured. The pH values of the lithium-, aluminum-, and phosphorus-containing aqueous solutions prepared in Comparative Examples 1 to 4, the pH values of the obtained raw material slurries, the compositions in the manufacturing process of the amorphous precursor powders, the analytical results and characteristic evaluation results, and the porosity of the sintered compacts are shown in Tables 1 to 4, similarly to Example 1. The amorphous precursor powder according to Comparative Example 1 is an amorphous precursor powder having a stoichiometric composition.
[0083] The powder obtained by crystallizing the amorphous precursor powder according to Comparative Example 1, which was obtained in the above-mentioned "(5) (Precursor Powder) Calcination Step, (II) Crystallization of Amorphous Precursor Powder," was subjected to XRD measurement under the measurement conditions described in Example 1. The obtained XRD spectrum is shown in the lower part of FIG.
[0084] The XRD spectrum of the powder having a NASICON-type crystal structure as the main phase according to Comparative Example 1 shown in the lower part of FIG. 3 is compared with that of LiGePO, an oxide having a NASICON-type crystal structure. 12 This was compared with ICDD PDF No. 01-080-1922. The peaks detected by the peak search method were in the ranges of 21.4±0.5°, 25.1±0.5°, 30.4±0.5°, 33.3±0.5°, and 34.0±0.5°, and were determined to belong to PDF No. 01-080-1922. Therefore, the powder having the NASICON-type crystal structure as the main phase according to Comparative Example 1 was found to contain lithium, aluminum, germanium, and phosphorus from the results of the composition analysis described above, and to have the NASICON-type crystal structure as the main phase from the results of the XRD measurement.
[0085] Furthermore, XRD measurement was carried out on the white precursor powder according to Comparative Example 1 obtained in the above-mentioned "(4) drying step" under the measurement conditions described in Example 1. The obtained XRD spectrum is shown in the lower part of Figure 4. The XRD measurement results showed a peak for NH4NO3, but no peaks for lithium compounds, aluminum compounds, germanium compounds, or phosphorus compounds.
[0086] (summary) The results in Tables 1 to 4 show that the porosity of the sintered molded body obtained by molding the amorphous precursor powder having the stoichiometric composition of Comparative Example 1 and firing it at 800°C was 33%, whereas the porosity of the sintered molded body obtained by molding the amorphous precursor powder containing excess lithium and phosphorus relative to the stoichiometric composition of Examples 1 to 3 and firing it at 800°C was 21 to 24%, indicating a significant decrease in porosity.
[0087] [Table 1] [Table 2] [Table 3] [Table 4]
Claims
1. An amorphous precursor powder comprising lithium, aluminum, germanium and phosphorus, The molar ratios of lithium, aluminum, germanium, and phosphorus atoms are expressed by the proportional formula Li:Al:Ge:P=(1+x+z):x:(2−x):(3+y), The amorphous precursor powder has a ratio of x, y, and z in the proportional formula of 0.0<x≦1.0, 0.1≦y≦0.8, and 0.2≦y / z≦0.
8.
2. 2. The amorphous precursor powder of claim 1, wherein the value of y is 0.1≦y≦0.
5.
3. 3. The amorphous precursor powder according to claim 1 or 2, wherein when 10 g of the amorphous precursor powder is heat-treated at 600° C. for 120 minutes in an air atmosphere and the powder is subjected to XRD measurement, it is confirmed that the powder has a NASICON type crystal structure as a main phase.
4. 3. The amorphous precursor powder according to claim 1, wherein the value of z is 0.125≦z≦2.
0.
5. A molded body obtained by molding the amorphous precursor powder according to claim 1 or 2.
6. A method for producing an amorphous precursor powder which becomes a powder having a NASICON type crystal structure as a main phase by heat treatment at 600° C. for 120 minutes in an air atmosphere, comprising the steps of: Obtaining a slurry containing lithium, aluminum, germanium and phosphorus; A calcination step of calcining the slurry at 300° C. or more and 500° C. or less to obtain an amorphous precursor powder, In the slurry, the molar ratios of lithium, aluminum, germanium, and phosphorus atoms are expressed by the proportional formula Li:Al:Ge:P=(1+x+z):x:(2−x):(3+y), The method for producing an amorphous precursor powder, wherein the slurry is prepared so that x, y, and z in the proportional formula satisfy 0.0<x≦1.0, 0.1≦y≦0.8, and 0.2≦y / z≦0.
8.
7. 7. The method for producing an amorphous precursor powder according to claim 6, wherein the step of obtaining the slurry comprises a step of mixing an aqueous solution containing germanium with an aqueous solution containing lithium, aluminum, and phosphorus.
8. The method for producing an amorphous precursor powder according to claim 7, wherein the aqueous solution containing lithium, aluminum and phosphorus has a pH value of pH 1 or more and pH 5.5 or less.
9. The method for producing an amorphous precursor powder according to claim 6 or 7, wherein the pH value of the slurry is from pH 1 to pH 6.
5.
10. A method for producing a sintered molded body, comprising the steps of compressing and molding a powder produced by the method for producing an amorphous precursor powder according to claim 6 or 7, and then sintering the powder to produce a sintered molded body having a NASICON crystal structure as a main phase.
11. A method for producing a powder, comprising the step of calcining a powder produced by the method for producing an amorphous precursor powder according to claim 6 or 7, thereby producing a powder having a NASICON crystal structure as a main phase.
Citation Information
Patent Citations
Ceramic base powder, method for producing all-solid-state battery, and all-solid-state battery
JP2020187897A
Amorphous lithium ion-conductive oxide powder and method for producing the same, and method for producing lithium ion-conductive powder having nasicon-type crystal structure
JP2021098643A